2019
DOI: 10.1111/oik.06099
|View full text |Cite
|
Sign up to set email alerts
|

Responses of plant phenology to nitrogen addition: a meta‐analysis

Abstract: Phenology is one of the most sensitive processes of plant in response to global change. Anthropogenic activities have considerably increased nitrogen (N) deposition, which significant affects plant phenology. Although numerous individual studies have been conducted, it remains controversial how N addition affects phenological stages, and a comprehensive understanding of how plant phenology responds to external N inputs remains elusive. To reconcile the differences, we conducted a meta‐analysis of 117 species t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 55 publications
3
32
0
Order By: Relevance
“…Phenology, or the timing of life history events, is critical to fitness and population persistence (Parmesan and Yohe, 2003; Cleland et al, 2007). While some species and populations exhibit little phenological plasticity (i.e., shift their phenology little in response to environmental variation), other species and populations respond strongly to temperature and precipitation (Visser and Both, 2005; Matthews and Mazer, 2016; Thackeray et al, 2016; Cremonense et al, 2017) and other environmental variables such as nutrient availability or competition (Smith et al, 2012; Xia and Wan, 2013; Du et al, 2019; Wang and Tang, 2019). Phenological plasticity may promote population growth (or limit population declines) in the face of climate change and has been associated with invasiveness and range size (Crawley et al, 1996; DeFalco et al, 2007; Willis et al, 2008, 2010; Cleland et al, 2012; Pearson et al, 2012; Wolkovich et al, 2013; Lustenhouwer et al, 2018; Zettlemoyer et al, 2019b; Reeb et al, 2020), suggesting that species that are less phenologically plastic may be more at risk of population declines and eventual extirpation (Møller et al, 2008; Willis et al, 2008; Forrest and Miller‐Rushing, 2010; Miller‐Rushing et al, 2010).…”
mentioning
confidence: 99%
“…Phenology, or the timing of life history events, is critical to fitness and population persistence (Parmesan and Yohe, 2003; Cleland et al, 2007). While some species and populations exhibit little phenological plasticity (i.e., shift their phenology little in response to environmental variation), other species and populations respond strongly to temperature and precipitation (Visser and Both, 2005; Matthews and Mazer, 2016; Thackeray et al, 2016; Cremonense et al, 2017) and other environmental variables such as nutrient availability or competition (Smith et al, 2012; Xia and Wan, 2013; Du et al, 2019; Wang and Tang, 2019). Phenological plasticity may promote population growth (or limit population declines) in the face of climate change and has been associated with invasiveness and range size (Crawley et al, 1996; DeFalco et al, 2007; Willis et al, 2008, 2010; Cleland et al, 2012; Pearson et al, 2012; Wolkovich et al, 2013; Lustenhouwer et al, 2018; Zettlemoyer et al, 2019b; Reeb et al, 2020), suggesting that species that are less phenologically plastic may be more at risk of population declines and eventual extirpation (Møller et al, 2008; Willis et al, 2008; Forrest and Miller‐Rushing, 2010; Miller‐Rushing et al, 2010).…”
mentioning
confidence: 99%
“…As a convention, former studies often divided grassland species into two groups of grasses and forbs or into four groups of grasses, sedges, forbs, and legumes (Wang & Tang, 2019). Existing research identified contrasting phenological responses of grasses and forbs to N addition (Cleland et al, 2006;Smith et al, 2012;Xia & Wan, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that forbs that include many different species did not correlate with any phenophases, and grasses only correlated with the length of growing season at a lower strength than expected. Since Cyperaceous plants can initiated life-history earlier under N enrichment (Ren et al, 2016) and include late-flower sedge (Stenström & Jónsdóttir, 1997), they can have significant impacts on the end of growing season and have been reported to perform differently with other groups (Wang & Tang, 2019). In fact, varying grasses may have significantly different responses or even in contrasting directions to environmental variations (e.g., perennial grasses and annual grasses),…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, plant phenology was divided into the following 10 stages: leaf‐out (stage 0), budding (stage 1), flowering (stage 2), post‐anthesis (stage 3), initiated fruiting (stage 4), expanding fruiting (stage 5), dehisced fruit (stage 6), disarticulated seeds (stage 7), post‐fruit leafing (stage 8) and leaf colouring (stage 9) (see Supporting Information Figure S2). Based on previous studies (Dunne et al., 2003; Sherry et al, 2007; Wang & Tang, 2019), the time difference between budding and flowering was defined as the flower bud duration, between flowering and post‐anthesis was defined as flowering duration, and between initiated fruiting and dehisced fruit was defined as fruiting duration in our study. The reproductive phase was calculated as the time between budding and disarticulated seeds, and growing season length was calculated as the time between leaf‐out and leaf colouring.…”
Section: Methodsmentioning
confidence: 99%